KEBIJAKAN PEMBATASAN USIA MEDIA SOSIAL SEBAGAI UPAYA PERLINDUNGAN ANAK DI ERA DIGITAL - Lulu Syakirah Alatas; Abdul Hadi; Adithya Tri Firmansyah R (DEVELOPMENT: Journal of Community Engagement, 2026)
The rapid growth of digital technology has increased social media use among adolescents, creating various challenges related to online safety, privacy, and exposure to inappropriate content. This community service activity aimed to enhance students’ understanding of social media age-restriction policies and strengthen their awareness of child protection in digital environments. The program was conducted at MAN 4 South Jakarta through legal counseling and digital literacy education using lectures, audiovisual presentations, interactive discussions, and question-and-answer sessions. The activity focused on introducing the provisions of the Regulation of the Minister of Communication and Digital Number 9 of 2026 concerning child protection in digital spaces, as well as the risks associated with irresponsible social media use. The results indicate that students demonstrated improved knowledge regarding age limitations for social media access, digital rights and responsibilities, privacy protection, and the potential impacts of cyberbullying and misinformation. Active participation during discussions also reflected growing awareness of the importance of responsible digital behavior. The program contributed to strengthening legal awareness and digital literacy among students, supporting broader efforts to create a safer and more child-friendly digital environment.